Treatment of Anogenital Warts: Siriraj Hospital Experience - Manopchai Thamkhantho; Chenchit Chayachinda (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
Objectives: To demonstrate the characteristics, treatment modalities and outcomes in the women presenting with Anogenital Warts (AGW) at Female STI Clinic, Siriraj Hospital.Materials and Methods: The outcomes of treatment in the patients presenting with AGW who had complete follow-up at Siriraj Female STI clinic in 2016 were reviewed. The patients with immunocompromised conditions such as systemic lupus erythematosus and human immunodeficiency virus infection were excluded from this study. Results: Two hundred and four of 217 women with AGW were eligible for this study. The mean age was 24.6 ± 5.2 years. Most of them were married and had sexual monogamy. Education levels were similar. Most of the AGWs were located outside the vagina and with ≤ 5 lesions (range 1-20). The diameter of warts was between 1 and 5 cm. The treatment modalities were 85% trichloroacetic acid (TCA) 131 (64.3%), 5% imiquimod 57 (27.9%), cryotherapy 8 (3.9%) and surgery 8 (3.9%). The median periods of treatment were 4, 8, 5 and 1 weeks for 85% TCA, 5% Imiquimod, Cryotherapy and Surgery, respectively. Treatment modalities were changed in the groups of 85% TCA and 5% Imiquimod, for 16.0% and 1.8%, respectively. Recurrence at 3 months after being cured was highest in the groups of 85% TCA (13.0%).Conclusion: Our results showed that 85% TCA, which is widely available, need four applications with 13% recurrence rate. Imiquimod took longer time for treatment but was associated with less recurrent. Cryotherapy and Surgery showed promising results but the data were limit.